PWE-129 Trends In Variceal Bleeding: A Single Centre Experience From 2006–2013. (9th June 2014) - Grant, C; Kemp, D; Beattie, M; Austin, A
Abstract : Introduction: Over the last decade, the numbers of patients presenting with chronic liver disease has risen. During this period the approach to the treatment of variceal bleeding has undergone important changes both internationally (adoption of early TIPSS in high risk cases), and locally with the development of a 24 h endoscopy service (2006), movement to single site hospital with enlarged intensive care capacity (2009), adoption of the Danis™ stent (2009) and a shift to carvedilol as the primary agent for prophylaxis (2013). We reviewed all episodes of variceal bleeding in the last 8 years to describe patient outcomes. Methods: All episodes of bleeding from oesophageal varices managed in the Liver Unit at Royal Derby Hospital from 2005 to mid 2013 were identified from clinical coding data – population served approx. 650, 000. A retrospective review of the patient records identified the aetiology and severity of liver disease, morbidity, mortality, endoscopy findings and episodes of rebleeding. Results: Each year between 17 and 31 patients presented with variceal bleeding. 5 day mortality fluctuated between 3–22% whereas 30 day mortality fell steadily from a peak in 2006 of 41% to 5% in 2012 (Figure 1 ). The reduction in mortality was in Child's B/C cirrhosis. Interestingly, the proportion of episodes in Child's A cirrhosis increased from 2009 onwards (7% of all bleeding episodes in 2009 to above 30% in 2013). 30 day mortality rates for Child's A did not improve but remained lower than for those with Child's B/C cirrhosis (mean 9.8% compared to 22.8% (2009–2013)). From 2007, there was a fall in frequency of rebleeding from 35% to below 10% in 2013. Only 3 high risk patients underwent an early TIPSS procedure, all after 2012. Conclusion: Variceal bleeding rates have remained surprisingly constant over 8 years despite the rise in admissions with chronic liver disease. Outcomes for acute variceal bleeding have improved which is likely the result of several organisational changes. Notably, rebleeding rates and 30 day mortality decreased even before the adoption of early TIPSS. Disclosure of Interest: None Declared.